Impact of Platelet Transfusion on Survival of Patients with Intracerebral Hemorrhage after Administration of Anti-Platelet Agents at a Tertiary Emergency Center - Suzuki, Yuhko (Public Library of Science, 2014)
This study examined the impact of platelet transfusion (PLT) on the survival of intracerebral hemorrhage (ICH) patients who had been administered anti-platelet agents (APA). This retrospective cohort analysis investigated 432 patients (259 men, 60%) who were newly diagnosed with ICH between January 2006 and June 2011 at the tertiary emergency center of Kitasato University Hospital. Median age on arrival was 67.0 years (range, 40–95 years). ICH was subcortical in 72 patients (16.7%), supratentorial in 233 (53.9%), and infratentorial in 133 (30.8%). PLT was performed in 16 patients (3.7%). Within 90 days after admission to the center, 178 patients (41.2%) had died due to ICH. Before the onset of ICH, 66 patients had been prescribed APA because of atherosclerotic diseases. Multivariate regression analysis indicated APA administration was an independent risk factor for death within 7 days (odds ratio, 5.12; P = 0.006) and within 90 days (hazard ratio, 1.87; P = 0.006) after arrival. Regarding the effect of a PLT in ICH patients with APA, no patient with PLT died. PLT had a survival benefit on patients with ICH, according to our analysis. Further prospective analysis is necessary to confirm the effects of PLT on survival in ICH with APA.